The expendables - Callaham, David, 1977-; Stallone, Sylvester; Lerner, Avi.; Templeton, Kevin King.; Thompson, John.; Schwarzenegger, Arnold; Willis, Bruce, 1955-; Lundgren, Dolph, 1959-; Statham, Jason, 1967-; Li, Jet, 1963-; Roberts, Eric, 1956-; Couture, Randy; et al. (Santa Monica, Calif. : Lions Gate Entertainment, 2010)
The Expendables are a tight-knit team of skilled combat vets turned mercenaries. Hired by a powerful covert operator, the team jets off to a small South American country to overthrow a ruthless dictator. Once there, they find themselves caught in a deadly web of deceit and betrayal. Using every weapon at their disposal, they set out to save the innocent and punish the guilty in this blistering action-packed thriller. Special features included.
Special features: "Before the Battle" Making of Featurette ; audio commentary with Sylvester Stallone ; deleted scene ; gag reel ; marketing archive.
Arnold Schwarzenegger, Bruce Willis, Dolph Lundgren, Jason Statham, Jet Li, Sylvester Stallone, Eric Roberts, Randy Couture, Steve Austin, David Zayas, Giselle Itie, Charisma Carpenter, Gary Daniels, Terry Crews, Mickey Rourke.
MPAA rating: R; for strong action and bloody violence throughout, and for some language.
DVD ; widescreen (2.40:1) ; 5.1 Dolby Digital EX.
English dialogue ; English and Spanish subtitles ; closed-captioned.
Keywords: Veterans -- Drama; Armed Forces -- Drama; Mercenary troops -- Drama; Revolutions -- Latin America -- Drama; Spanish language materials; Feature films; Video recordings for the hearing impaired; Video recordings for the hearing impaired